Divisão social e racial do trabalho: A questão da imobilidade profissional do trabalhador negro no Brasil. - BRITO, Daniel Santos de (2023)
The present work deals with the professional immobility of the black worker in the Brazilian labor market, in order to expose the path that black people have taken from slavery to free labor relations in the competitive market, aiming to highlight the precarious way in which black people are inserted in the Brazilian labor market, in addition to identifying the racial barriers that prevent their professional ascension, relating this reality to the capitalist production model and racism. To this end, we deal with the way in which the social and racial division of labor developed in the socioeconomic formation of Brazil, highlighting that the result of this racial hierarchy in the Brazilian labor market contributes to the professional immobility of black workers in the most significant jobs in the occupational structure of society. As a result, we revisit the main racial ideologies that, in the restructuring of the world market's productive process, negatively influenced the absorption of black people in the transition from slave labor to free labor in Brazil. Finally, we demonstrate that racism is one of the mechanisms of social and professional immobility operating in Brazil that contribute to maintaining the privileges of the racially dominant group while at the same time serving to selectively exclude the racially subordinated group from spaces of power and decision-making.